gbalkam wrote:

(2x+3)(3x+5) is actually the same as (2x+3) multiplied by (3x+5) = (6x +15)

That is wrong. It should be:

$ \displaystyle \begin{array}{rcl}(2x+3)(3x+5) &=& (2x)(3x+5)+3(3x+5) \\ {} &=& 6x^2+10x+9x+15 \\ {} &=& 6x^2+19x+15\end{array}$

gbalkam wrote:

Remember in this case (2x+3) is not an equation, it is a value (solution to an equation)

It's neither an equation nor a solution. What it is is an

**expression** involving the unknown

*x*.

gbalkam wrote:

Hopefully I remembered that correctly.

Nope.